2021
DOI: 10.1038/s41598-021-93026-w
|View full text |Cite
|
Sign up to set email alerts
|

Deep-learning framework and computer assisted fatty infiltration analysis for the supraspinatus muscle in MRI

Abstract: Occupation ratio and fatty infiltration are important parameters for evaluating patients with rotator cuff tears. We analyzed the occupation ratio using a deep-learning framework and studied the fatty infiltration of the supraspinatus muscle using an automated region-based Otsu thresholding technique. To calculate the amount of fatty infiltration of the supraspinatus muscle using an automated region-based Otsu thresholding technique. The mean Dice similarity coefficient, accuracy, sensitivity, specificity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrate that 3D muscle volumetry should be preferred in patients with full-thickness SSP tendon tears when the muscle volume needs to be quantified preoperatively in order to estimate the postoperative success rate after tendon repair procedures. This is in accordance with previous studies [ 17 ] and is important since various previous experimental and clinical studies have shown that significant SSP muscle atrophy is an important adverse prognostic factor affecting patients’ outcomes in addition to other conditions, e.g., fatty infiltration or severe tear size [ 8 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 92%
“…Just recently, another study analysed the use of deep-learning framework to study occupation ratio and fatty infiltration of the supraspinatus muscle [ 30 ]. Scapular sagittal Y-view MRI images (T1-weighted) were used as baseline for obtaining reliable indicators of the supraspinatus muscle status.…”
Section: Resultsmentioning
confidence: 99%
“… 13 , 25 However, in its current application, occupation ratio relies on manual tracing of a single muscle cross-section and is limited to the supraspinatus muscle with its well-defined fossa. Future development of automated muscle segmentation algorithms 17 applied to 3D muscle volumes, 8 using quantitative MRI such as Dixon to measure fat fraction 6 and acquisition of age and gender normative data on muscle volumes 25 and fat fractions, would greatly enhance accurate assessment of shoulder muscle pathology.…”
Section: Discussionmentioning
confidence: 99%